Comparison of Transcriptional Response of C3 and C4 Plants to Drought Stress Using Meta-Analysis and Systems Biology Approach - Tahmasebi, Ahmad; Niazi, Ali (Frontiers in Plant Science, 2021)
Drought stress affects a range of plant processes. It is still not well-known how C3 and C4 plants respond to drought. Here we used a combination of meta-analysis and network analysis to compare the transcriptional responses of Oryza sativa (rice), a C3 plant, and Zea mays (maize), a C4 plant, to drought stress. The findings showed that drought stress changes the expression of genes and affects different mechanisms in the C3 and C4 plants. We identified several genes which were differentially expressed (DEGs) under stress condition in both species, most of which are associated with photosynthesis, molecule metabolic process and response to stress. Additionally, we observed that many DEGs physically located within QTL regions associated with C isotope signature (d13C), photosynthetic gas exchange and root characteristics traits. Through the gene co-expression and differential co-expression network methods, we identified sets of genes with similar and different behaviors among C3 and C4 plants during drought stress. This result indicates that MAPK signaling pathway plays an important part in the differences between the C3 and C4 species. The present study provides a better understanding of the mechanisms underlying the response of C3 and C4 plants to drought stress, which may useful for engineering drought tolerance in plants.